1998
DOI: 10.1093/intimm/10.8.1093
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and functional characterization of a panel of cytotoxic murine NK cell clones that are heterogeneous in their enhancement of Ig secretion in vitro

Abstract: NK cells not only function as cytotoxic effector cells, but also have immunoregulatory roles including the enhancement of Ig secretion. To have a stable and uniform population of NK cells to study their role in Ig secretion, we generated murine NK clones. Thus, culture of splenocytes from mice that were homozygous for a mutation in the p53 tumor suppressor gene (p53-KO) with IL-2 and poly(IC) resulted in a long-term NK line, from which four stable clones were derived. This approach also yielded a long-term NK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Direct interaction between B and NK cells under activated conditions are supported by several studies, particularly in mouse models (15)(16)(17)(18). Evidence from human studies suggests that NK cells and B cells can spontaneously interact in vitro, as demonstrated by conjugate formation and activation of the interacting cells (11).…”
Section: Cd2mentioning
confidence: 94%
“…Direct interaction between B and NK cells under activated conditions are supported by several studies, particularly in mouse models (15)(16)(17)(18). Evidence from human studies suggests that NK cells and B cells can spontaneously interact in vitro, as demonstrated by conjugate formation and activation of the interacting cells (11).…”
Section: Cd2mentioning
confidence: 94%
“…Regarding immortalized NK lines, there are a few studies on generation of murine NK [85][86][87][88][89] and human NK [90] cell lines. Dr. Tian and coworkers recently summarized the NK cell lines in cancer immunotherapy [48].…”
Section: Remaining Challengesmentioning
confidence: 99%
“…While immunization of mice that have combined T and NK deficiency with TI-2 antigens results in normal IgM antibody responses (239) (Q. Vos, J. J. Mond, unpublished results), Yuan and co-wokers have shown that activation of NK activity by administration of polyinosinic-polycytidylic acid (225) or tumor cells (240) can modulate in vivo TI-2 responses. A series of studies has described the ability of NK to stimulate Ig secretion in vitro (241)(242)(243)(244)(245)(246)(247). We have shown that NK-cell secretion of IFN-g is a critical parameter for the induction of Ig secretion in B cells stimulated with ad-dex and IL-2, and that the level of modulation of Ig secretion by a panel of murine NK clones correlates with their level of IFN-g secretion (244)(245)(246)(247).…”
Section: Modulation Of Ti-2 Responses By Nk Cellsmentioning
confidence: 99%
“…A series of studies has described the ability of NK to stimulate Ig secretion in vitro (241)(242)(243)(244)(245)(246)(247). We have shown that NK-cell secretion of IFN-g is a critical parameter for the induction of Ig secretion in B cells stimulated with ad-dex and IL-2, and that the level of modulation of Ig secretion by a panel of murine NK clones correlates with their level of IFN-g secretion (244)(245)(246)(247). In addition, we have preliminary evidence for NK secretion of additional B-cell stimulatory cytokines, since B-cell stimulation in the presence of supernatants of some of our NK clones showed a kinetics of Ig induction and an Ig-isotype pattern that could not be induced by purified IFN-g itself (Q. Vos, J. J. Mond, unpublished results).…”
Section: Modulation Of Ti-2 Responses By Nk Cellsmentioning
confidence: 99%